Determinants of Financial Stress in Emerging Market Economies - Cyn-young Park; Rogelio V. Mercado (Asian Development Bank (ADB), 2013)
The global financial crisis of 2008-2009 illustrates how financial turmoil in advanced economies could trigger severe financial stress in emerging markets. Previous studies dealing with financial crises and contagion show the linkages through which financial stress are transmitted from advanced to emerging markets. This paper extends the existing literature on the use of financial stress index (FSI) in understanding the channels of financial transmission in emerging market economies. Using FSI of 25 emerging markets, our panel regression estimates show that not only advanced economies FSI, but also regional and nonregional emerging market FSIs significantly increase domestic financial stress. Our findings also suggest that there is a common regional factor significantly affecting domestic FSI in emerging Asia and emerging Europe. Furthermore, the results from a structural vector autoregression model with contemporaneous restrictions indicate that although a domestic financial shock still accounts for most of the variation in domestic FSI, regional shocks play an important role in emerging Asia.
hdl:11540/4225
Keywords: F30; G01; G15; 330; financial stress index; financial contagion; emerging market economies